Pseudomonas aeruginosa LasI/RhlI quorum sensing system controls protease-mediated autoaggregation behavior, cell envelope characteristics and extracellular proteome responses - Eriksson, Albin; Turkina, Maria V.; Ntzouni, Maria; Magnusson, Karl-Eric; Vikström, Elena (Frontiers in Microbiology, 2026)
Quorum sensing (QS) is an intercellular communication mechanism employed by the opportunistic bacteria Pseudomonas aeruginosa to regulate processes beneficial to the longevity of the community and related to its pathogenicity. The LasI/Rhl circuits of the quorum-sensing (QS) network operate through N-acyl-L-homoserine lactones (AHL) and appear at the top in the QS hierarchy. In natural habitats and host environments, bacteria exist and transit between different modes of lifestyle: planktonic single cells, suspended multicellular aggregates, and surface-attached biofilm communities. Using P. aeruginosa PA14 as a model, we determined the contribution of the master regulator LasI/RhlI QS system to multicellular community autoaggregation in liquid, ultrastructure and fitness characteristics of the cell envelope, and extracellular proteome responses, employing phenotypic assays, light imaging, high-resolution transmission electron microscopy and quantitative mass spectrometry-based proteomics and bioinformatics. Wild-type bacteria with a functional QS system were more effective in the protease-mediated autoaggregation than the lasI-/rhlI- mutant, lacking the production of AHL molecules and associated virulence traits. AHL-dependent communication impacted cell envelope characteristics, including ultrastuctural curvature and tolerance to membrane-damaging and antimicrobial agents. Moreover, the LasI/RhlI QS system perturbed the extracellular abundance of a total of 545 extracellular proteins during late exponential and early stationary growth phases. We allocated most of these differentially expressed proteins to the following large functional groups: metabolism; transcription and translation; transport and secretion systems; cell envelope integrity; redox processes; invasiveness and toxicity; and motility. Remarkably, approximately 95% of the extracellular proteome was upregulated in the lasI–/rhlI– mutant compared with the wild type, and these levels were restored to wild type-status when AHL was added. We observed a crucial contribution of the LasI/RhlI QS system to the protease-mediated community autoaggregation in P. aeruginosa PA14. Mechanistically, this was accompanied—through a sophisticated and multifactorial process—by differential expression of an array of components in the secreted proteome involved in both pathogenicity-specific and global readjustments in the homeostasis within the population. By fine tuning the LasI/RhlI system, Pseudomonas can regulate its pathogenic potential and long-term survival in different hosts and habitats.